Tibetan <ḥ-> as a plain initial and its place in old Tibetan phonology - Hill, Nathan W. (2024)
Beginning with de Kőrös (1834) many researchers have held that the Tibetan letter འ <ḥ> as a simple initial represents a voiced fricative. In 1881 Jäschke initiated an alternative view, which holds that this letter has no phonetic value, instead representing vocalic onset. An examination of the reflexes of relevant Old Tibetan words in the modern Tibetan languages, the order of the Tibetan alphabet, and Old Tibetan phonotactics confirms the earlier tradition of scholarship. It is concluded in addition that in Old Tibetan <ḥ> represented a voiced velar fricative in all syllable positions and that the Common Tibetan values of prenasalization before consonants and vowel lengthening as a final are due to sound change from Old Tibetan to Common Tibetan.